Interventional spine procedures under CT guidance: How to reduce patient radiation dose without compromising the successful outcome of the procedure?. (March 2017) - Greffier, Joël; Pereira, Fabricio R.; Viala, Pierre; Macri, Francesco; Beregi, Jean-Paul; Larbi, Ahmed
Highlights: CT-scan is an important tool for spinal interventional radiology. Patient dose is not negligible and requires optimization of procedures. Optimization consists in dose reduction with suitable image-quality. Optimization consist on reducing kV/mAs, using i-sequence and limiting i-spiral. Abstract: This technical note proposes a method to reduce radiation dose for spine interventions under CT guidance without compromising the successful outcome of the procedure. Two consecutive periods of 14 months before and after optimization were investigated with 162 and 440 patients, respectively. By optimizing the acquisition parameters (decreased kV and mAs) and appropriately adjusting the reconstruction (kernels, slice thickness, etc) and visualization parameters, image quality was maintained suitable to perform the procedure. By reducing both kV and mAs, dose was reduced by 72% on fluoroscopy mode (i-fluoro) and sequential mode (i-sequence). Moreover, dose was reduced by 58% on helical mode (i-spiral). Depending on the radiologist, the fluoroscopy time was decreased by between 37% and 56%. Acquisitions with i-sequence were less irradiating than the i-fluoro or the i-spiral modes. Radiation doses were reduced by 65% for infiltrations, 51% for vertebral expansions, and 56% for bone biopsies. Median (1st quartile; 3rd quartile) effective dose were 2.1 (1.3; 3.5) mSv, 10.8 (6.7; 18.3) mSv for and 3.0 (2.4; 4.3) mSv, respectively. Radiologists reported "satisfactory" image quality. During interventional spine procedures under CT scan, reducing kV and mAs associated with the use of i-sequence substantially reduces patient dose.